Preparation and Drug Release Profile of Chitosan–Siloxane Hybrid Capsules Coated with Hydroxyapatite - Yuki Shirosaki; Yasuyo Tsukatani; Kohei Okamoto; Satoshi Hayakawa; Akiyoshi Osaka (Pharmaceutics, 2022)
Chitosan is a cationic polymer that forms polymerized membranes upon reaction with anionic polymers. Chitosan−carboxymethyl cellulose (CMC) capsules are drug delivery carrier candidates whose mechanical strength and permeability must be controlled to achieve sustained release. In this study, the capsules were prepared from chitosan−γ-glycidoxypropyltrimethoxysilane (GPTMS)−CMC. The mechanical stability of the capsules was improved by crosslinking the chitosan with GPTMS. The capsules were then coated with hydroxyapatite (HAp) by alternately soaking them in calcium chloride solution and disodium hydrogen phosphate solution to prevent rapid initial drug release. Cytochrome C (CC), as a model drug, was introduced into the capsules via two routes, impregnation and injection, and then the CC released from the capsules was examined. HAp was found to be deposited on the internal and external surfaces of the capsules. The amount of CC introduced, and the release rate were reduced by the HAp coating. The injection method was found to result in the greatest CC loading.